Fashion - Breward, Christopher (Oxford University Press, 2003)
Following 150 years of fashion, Christopher Breward offers a catholic view of this colorful and flamboyant universe, describing its trends, products, and inhabitants. From Haute Couture, High Street, and developing fabric technology to such stars of the fashion heavens as Coco Chanel, Giorgio Armani, and Alexander McQueen, Breward explores territories far beyond style and function. He sees more than just an industry, giving voice to the larger cultural phenomenon fashion has become